Trauma exposure and stress-related disorders in inner city primary care patients - Gillespie, Charles F.; Bradley, Bekh; Mercer, Kristie; Smith, Alicia K.; Conneely, Karen; Gapen, Mark; Weiss, Tamara; Schwartz, Ann C.; Cubells, Joseph F.; Ressler, Kerry J. (General hospital psychiatry, 2009)
This study was undertaken to increase understanding of environmental risk factors for posttraumatic stress disorder (PTSD) and major depressive disorder (MDD) within an urban, impoverished, population. This study examined the demographic characteristics, patterns of trauma exposure, prevalence of PTSD and MDD, and predictors of posttraumatic stress and depressive symptomatology using a verbally presented survey and structured clinical interviews administered to low-income, primarily African-American (>93%) women and men seeking care in the primary care and obstetrics–gynecology clinics of an urban public hospital. Of the sample, 87.8% ( n=1256) reported some form of significant trauma in their lifetime. Accidents were the most common form of trauma exposure followed by interpersonal violence and sexual assault. Childhood level of trauma and adult level of trauma separately, and in combination, predicted level of adult PTSD and depressive symptomatology. The lifetime prevalence of PTSD was 46.2% and the lifetime prevalence of MDD was 36.7%. These data document high levels of childhood and adult trauma exposure, principally interpersonal violence, in a large sample of an inner-city primary care population. Within this group of subjects, PTSD and depression are highly prevalent conditions.